Health Belief Model and Individualist-Collective Culture on Compliance with Health Protocols - Afia Meliana; Devi Jatmika (School of Industrial and System Engineering, Telkom University, 2021)
The COVID-19 pandemic has spread amost all over the world including Indonesia since March 2020,causing many people got infected. Large-Scale Social Restrictions (PSBB) was enforced, whereas activitiesoutside the home were restricted. After the PSBB period is revoked, people can do actvities outside the homewhile still adhering to health protocols. Compliance with health protocols cannot be separated from publicperceptions of health, namely Health Belief Model. In addition, culture also plays a role in determining one’sbehaviour. This study aimed to examine the relationship between the health belief model and collectiveculture with health protocol compliance. The research method used was a quantitative research method withcorrelation analysis techniques. The number of respondents in this study was 408 people, with age range of20-39 years old and live in Jakarta. The results of the study found that perceivd susceptibiliy, perceivedseverity, perceived benefits, perceived barriers, cues to action, self-efficacy had a relationship with healthprotocol compliance and the most significant correlation was perceived susceptibility. The results alsorevealed that horizontal individualism, vertical individualism, horizontal collective, vertical collective had arelationship ith health protocol compliance ant the most significant relationship is horizontal collective andvertical collective. This research concluded the more someone feels vulnerable being exposed to COVIDand the collective culture that adheres health protocols in the group, the higher compliance.